2002
DOI: 10.1002/14651858.cd003840
|View full text |Cite
|
Sign up to set email alerts
|

Eradication therapy for peptic ulcer disease in Helicobacter pylori positive patients

Abstract: б О л е з н и с е Р д ц а и с О с у д О в 41 а.а. Михайлов 1 , а.М. Шилов 2 , а.а. спасский 1 1 ФГУ 2-й Центральный военный клинический госпиталь им. П.В. Мандрыка, Москва 2 ГБОУ ВПО 1-й Московский государственный медицинский университет им. И.М. Сеченова, ФППОВ, кафедра «Неотложные состояния в клинике внутренних болезней» отечеСтвенный и зарубеж ный опыт применени я препарата Физиотенз ® в лечении «заболеваний цивилизации» резюме В статье обобщаются возможности моксонидина (Физиотенз®) -одного из наиболее час… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 10 publications
0
73
0
4
Order By: Relevance
“…H pylori is the key factor in peptic ulcer development and eradication is recommended for both DUs and GUs, as it has been shown that H pylori eradication effectively achieves ulcer healing rates of >90% 151 152. Moreover, prolonged acid inhibition with PPI is not required after successful H pylori eradication in uncomplicated DU 153 154…”
Section: Management Of H Pylori Infection (Workhop 2)mentioning
confidence: 99%
“…H pylori is the key factor in peptic ulcer development and eradication is recommended for both DUs and GUs, as it has been shown that H pylori eradication effectively achieves ulcer healing rates of >90% 151 152. Moreover, prolonged acid inhibition with PPI is not required after successful H pylori eradication in uncomplicated DU 153 154…”
Section: Management Of H Pylori Infection (Workhop 2)mentioning
confidence: 99%
“…78 Eradication therapy for Helicobacter pylori infection has been shown to be effective for pylori peptic ulcer disease. 49 Gastrointestinal haemorrhage…”
Section: Peptic Ulcermentioning
confidence: 99%
“…The prevalence increases with age and lower socio-economic status and is higher in more northerly latitudes 1 , 2. Up to 95% of patients with proven duodenal ulcers and 70% with gastric ulcers have such infection 3. Eradication of H. pylori infection using a combination of antibacterial and antisecretory therapy is more effective in achieving sustained healing of ulcers than antisecretory therapy alone 3.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 95% of patients with proven duodenal ulcers and 70% with gastric ulcers have such infection 3. Eradication of H. pylori infection using a combination of antibacterial and antisecretory therapy is more effective in achieving sustained healing of ulcers than antisecretory therapy alone 3. In patients with bleeding ulcers, such eradication therapy reduces the rate of recurrent bleeding from around 20% to 2.9% 4…”
Section: Introductionmentioning
confidence: 99%